Niche partitioning between river shark species is driven by seasonal fluctuations in environmental salinity - Dwyer, Ross G.; Campbell, Hamish A.; Cramp, Rebecca L.; Burke, Colin L.; Micheli‐Campbell, Mariana A.; Pillans, Richard D.; Lyon, Barry J.; Franklin, Craig E.; Killen, Shaun (Functional ecology, 2020)
Tropical rivers and estuaries are highly dynamic environments, where environmental conditions change dramatically over spatial and temporal scales. This creates both physiological and ecological challenges for euryhaline elasmobranchs, where fluctuations in salinity can impact not only osmoregulatory function but also the ability to find and acquire prey. We investigated how spatial and temporal variation in environmental salinity influences physiological homoeostasis, habitat utilization and migration timing in two euryhaline carcharhinid sharks within a tropical river in northern Australia. Neonate and juvenile bull sharks Carcharhinus leucas and speartooth sharks Glyphis glyphis were tracked over a 4‐year period using implanted acoustic tags and an array of hydrophone receivers. Tissue samples were also collected from captured sharks and analysed for interspecific differences in plasma osmolarity, urea and electrolyte (Na+ and K+) concentrations and the stable isotopes δ13C and δ15N. We discovered that immature C. leucas and G. glyphis segregate spatially along a salinity gradient between September and December, where the mean volume of intersection between species dropped as low as 0.01. While G. glyphis used higher salinity environments (mean salinity = 19.22) located between 30 and 70 km from the mouth of the estuary, C. leucas occupied freshwater reaches (mean salinity = 1.98) between 60 and 110 km upstream. Plasma osmolarities of both species were always hyperosmotic to the environment, with electrolyte concentrations maintained within a narrow range independent of environmental osmolarities. At the onset of the wet season, both C. leucas and G. glyphis undertook a coordinated downstream migration towards the lower estuary before returning upstream. Carcharhinus leucas blood tissues were more enriched in δ15N and δ13C than samples collected from similar size G. glyphis, suggesting that these species not only spatially segregate within low salinity habitats but also prey on different dietary resources. Furthermore, a loss of enriched isotopic values in fin tissue with increasing body length provides further support for marine use by adult sharks in conjunction with dependence on rivers as important nursery habitat. Our results illustrate the importance of long‐term integrative studies into resource competition and the significance of discrete brackish habitats for threatened euryhaline elasmobranchs. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.